Development of a virtual assistant using facebook messenger for the improvement of customer service at the private university - Condori Quispe, William (2019)
The present investigation seeks to implement a customer service in virtual environments in the social network Facebook through its Messenger communication service to provide a rapid level of responses and thus improve the service provided by the Professional School of Engineering Of Systems of the Private University of Tacna. It was decided to use a virtual assistant, since it is a channel in which the user can perform a query in conversation mode making it a very friendly channel. Thus, the virtual assistant was developed in the messenger service "Messenger" of the Professional School of Systems Engineering of the Private University of Tacna, whose function is to provide the requested information to the respective users, attending their queries of a Timely and effective manner. This information will be managed in a content manager which will provide the user with a friendly and simple interface. Messenger was selected as a messaging platform, since it has a greater number of users than other services, in addition to having special controls that make possible a better interaction between the assistant and the user. The use of the virtual assistant brought with it an improvement in the quality of customer service for the Professional School of Systems Engineering since there is a service available 24 hours a day and every day of the year, in addition to Display useful content for the university student community and for prospective students.